The Carioca High and Low Conditioned Freezing Lines: A New Animal Model of Generalized Anxiety Disorder - Gomes, Vitor de Castro; Silva, Carlos Eduardo Barroso; Landeira-Fernandez, J. (IntechOpen, 2011)
None